FarmDESIGN: Changing Ethiopian farming practices through sustainable intensification pathways - Abera, Wuletawu; Ebrahim, Mohammed; Ayehu, Getachew; Eshetae, Meron Awoke (2025)
In 2023 and 2024 more than 132 farmers adopted more sustainable practices, including diversified crops, forages, and poultry, which boosted yields, income, improved household nutrition, and promoted soil health. The Alliance of Bioversity International and CIAT-led FarmDESIGN optimization and exploration modeling tool was used with communities to explore and implement optimized farming practices. These incremental changes transformed local farming systems, advancing food and nutrition security while increasing the synergy between interventions and fostering environmental sustainability.